Regulator or Controller: A Five-Year Analysis of the Cat and Mouse Games between the Uganda Communications Commission and Broadcasters in Uganda - Walyemera, Daniel (Elsevier BV, 2021)
This article examines the conduct of the broadcasting regulator in Uganda. It considers whether the law governing the Uganda Communications Commission is in tandem with international human rights standards. This is in specific regard to media freedoms and other associated human rights. The major conclusion is that Uganda’s broadcasting regime is ambiguous and is used as a tool to facilitate partisan political interests. As a consequence, the said regime does not meet international human rights standards. The article recommends reform of the legal regime, including the operationalization of the Uganda Communications Tribunal to curb the arbitrary directives of the Uganda Communications Commission to radio, television and online broadcasters in Uganda.